European Union cohesion project characteristics and regional economic growth - Zsolt M. Darvas; Jan Mazza; Catarina Mid\~oes (Bruegel, 2021)
Due to problems with existing methodologies that aim to identify the causal impact of European Union cohesion policy on economic growth, we adopted a novel methodology. We first estimated 'unexplained economic growth' by controlling for the influence of various region-specific factors, and then analysed its relationship with about two dozen characteristics specific to projects carried out in various regions in the context of EU cohesion policy. We found that the best-performing regions have on average projects with longer durations, more inter-regional focus, lower national co-financing, more national (as opposed to regional and local) management, higher proportions of private or non-profit participants among the beneficiaries (as opposed to public-sector beneficiaries) and higher levels of funding from the Cohesion Fund. No clear patterns emerged concerning the sector of intervention.
Keywords: C21; O47; R11; 330; EU cohesion policy; growth determinants; regional convergence; project characteristics